The Effect of Alkali Treatment on Chemical and Physical Properties of Ichu and Cabuya Fibers - Tenazoa C. (2021)
Ichu and Cabuya were characterized and the effect of alkali treatment on the chemical and physical properties of these fibers was studied. This treatment was carried out to remove non-cellulosic components in order to improve the adhesion of these fibers to be used as reinforcing composites since they are currently being tested in polymer matrix composites. The chemical properties were investigated through TAPPI Standards and FTIR spectroscopy. The physical properties (microfibrillar angle and density) were analyzed through polarized light microscopy and a gas pycnometer, respectively. The results show that with this chemical treatment, it is possible to remove 53.9% of lignin and 22.7% of hemicellulose for Ichu fiber and 50.7% and 91.7%, respectively, for Cabuya. Besides, it was found that the microfibrillar angle is not affected by this chemical treatment since its effect is only superficial. In addition, SEM images show that Ichu fiber has amorphous silica particles in its surface, in which it becomes a potential fiber for cement composites. © 2019 Taylor & Francis.